SKELETAL MUSCLE METABOLIC FLEXIBILITY IMPAIRMENTS IN RESPONSE TO LIPID WITH OBESITY : EFFECT OF EXERCISE TRAINING - Battaglia, Gina (East Carolina University, 2012)
Obese individuals exhibit skeletal muscle metabolic inflexibility by failing to increase fat oxidation and genes linked with mitochondrial biogenesis in response to a high-fat diet (HFD) and lipid incubation in cell culture. Exercise training can increase skeletal muscle fatty acid oxidation (FAO) and mitochondrial content in the skeletal muscle of the obese, although whether it can normalize the response to excess lipid is unclear. The purpose of this dissertation was to determine whether metabolic flexibility in response to lipid could be rescued by short-term aerobic exercise training (study 1) and chemically uncoupling primary human skeletal muscle cells (HSkMC) to increase cell energy expenditure (study 2) in obese skeletal muscle. The hypotheses were that 1) obese individuals would exhibit skeletal muscle metabolic inflexibility in response to a 3d eucaloric high-fat diet (HFD; 70% total calories) in study 1, a defect that would persist in response to 24h lipid incubation in HSkMC (study 2); and 2) 10 consecutive days of aerobic exercise training (study 1), and mild uncoupling in vitro (study 2) would normalize the response to excess lipid in the skeletal muscle of obese individuals. Unlike the lean, obese individuals did not increase skeletal muscle FAO in response to a 3d HFD while sedentary (study 1) and did not increase protein content of Complex I, Complex III, and COX IV in response to 24h lipid incubation in HSkMC (study 2), supporting our hypothesis of lipid-induced metabolic inflexibility in obese skeletal muscle. Exercise training combined with a HFD produced a similar increase in FAO and citrate synthase (CS) activity in lean and obese individuals (study 1), indicating that HFD-induce metabolic flexibility was restored with exercise training regardless of obesity status. Incubation with the chemical uncoupler FCCP and lipid exhibited a treatment effect for Complex I and Complex III, although the latter appeared to be driven by the robust lean response, and increased COX IV content in the lean only. Therefore, lipid-induced metabolic inflexibility is persistent in cell culture, and increasing energy expenditure in vitro does not fully restore the response to lipid in a manner similar to in vivo exercise training.
Keywords: Kinesiology; Physiology; Exercise; Lipids; Mitochondria; Skeletal muscle; Biology, Physiology; Obesity; Musculoskeletal system; Exercise--Physiological aspects; Lipids--Metabolism